Perubahan Beberapa Sifat Kimia Ultisol Akibat Aplikasi Macam Bokasi pada Pertumbuhan Jagung - Yadi Jufri (Jurnal Agrista, 2006)
Some of Changes Ultisol Chemical Properties Caused Kinds of Bokasi Application on Maize GrowthABSTRACT. The main problem on ultisol was low of soil nutrient containt, that was caused of Ultisol chemical properties less. The research aim to study the effect kinds of organic matter as bokasi from to improved Ultisol chemical properties. The research was used Factorial Randomized Block Design, there were kinds of bokasi and fertilizer dosages. Kinds of bokasi were sawdust bokasi, rice straw bokasi and stem of soil palm bokasi. Applied fertilizer dosages were 10, 15, and 20 ton ha-1. There were 9 treatment combination with 3 replications, so that there were 27 experimental unit and the research consist of 2 experiment series. The first series was analysis of chemical properties and the second series was applied in maize growth observation. The research result show that was kinds of bokasi giving the effect to Ultisol chemical properties. Using of rice straw bokasi were giving the highest effect and then sawdust bokasi and the less one was stem of soil palm bokasi. Difference dosage treatment was giving the significant effect to ultisol chemical properties. Using of 20 ton ha-1 was giving the highest effect of Ultisol chemical properties. Kinds of bokasi was giving the significant effect to plant height, dry weight of up plant. Interaction between kinds of bokasi and dosages treatment were not giving the significant effect to all observation because the observation was short time.